PROGRAM FISIOTERAPI PADA KONDISI TENDINITIS SUPRASPINATUS: A CASE REPORT - Andera Prastina Sukmawati; Evi Oktaviani; Gede Agus Putra Wiranata; Anindhita Mella Pratama; Ahmad Dhiya Ul’haq; Arif Pristianto (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Supraspinatus tendinitis is a condition where there is inflammation of the supraspinatus tendon caused by repeated friction at the same time. This occurs because of the overlap between the supraspinatus muscle and the tendon of the head of the biceps longus. This situation can also be caused by direct injury to the shoulder or overuse trauma to the shoulder. This study uses the case report method (case study) conducted on patients with supraspinatus tendinitis at UPT Puskesmas Ngawi which was carried out in June 2022. In this case the patient experienced pain, limited joint range of motion (LGS), decreased muscle strength and limited functional activity. daily. The physiotherapy program given in this case is Ultrasound therapy, Infra Red and exercise therapy in the form of Range of Motion Exercise, Strengthening Exercise, Mobilization with Movement and Scapular Stabilization Exercise. After 5 times of therapy, the results were a decrease in pain, an increase in the LGS shoulder joint, and an increase in muscle strength. Functional activity ability was calculated using the Shoulder Pain And Disability Index (SPADI) index and the results showed an increase in functional activity in the shoulder. The combination of programmed physiotherapy interventions in the form of Ultrasound therapy, Infra Red, and exercise therapy in the form of Range of Motion Exercise, Strengthening Exercise, Mobilization with Movement and Scapular Stabilization Exercise can overcome the problems caused by supraspinatus tendinitis conditions.Keywords: Tendinitis supraspinatus, ultrasound therapy, exercise therapy, SPADI